2022
DOI: 10.2147/opto.s379659
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Perceptions Towards Hand Hygiene of Optometry Students Pre- and Peri-COVID-19 at a Tertiary Institution in Johannesburg, South Africa

Abstract: Purpose Limited research has been completed relating to the knowledge, attitudes and practices (KAP) towards hand hygiene in optometry. The necessity of identifying possible gaps in the cycle of the optometric examination that may have an impact on standard hygiene practices is essential, especially seen in the context of the COVID-19 pandemic. The purpose of the study was to determine if optometry students’ KAP towards hand hygiene changed pre- and peri-COVID-19 to minimize the risk of possible i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 36 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Limited information exists on the impact of hand hygiene education and awareness interventions in South Africa, particularly on changing hand hygiene behaviors among health science students [ 11 , 12 , 13 , 22 , 23 , 24 ]. In previous research, we performed an analytical examination of hand hygiene practices among clinic interns and their patients, utilizing GloGerm™ as a proxy for microbial contaminants, in which we showed that insufficient hand hygiene practices were discernible, based on participants’ hand washing skills after GloGerm™ exposure and their facial expressions and verbal feedback [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Limited information exists on the impact of hand hygiene education and awareness interventions in South Africa, particularly on changing hand hygiene behaviors among health science students [ 11 , 12 , 13 , 22 , 23 , 24 ]. In previous research, we performed an analytical examination of hand hygiene practices among clinic interns and their patients, utilizing GloGerm™ as a proxy for microbial contaminants, in which we showed that insufficient hand hygiene practices were discernible, based on participants’ hand washing skills after GloGerm™ exposure and their facial expressions and verbal feedback [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have highlighted this concern in some of our previous studies and have shown that despite providing university students with hand hygiene education, a significant number of bacterial cells persisted on their hands post-intervention. This discrepancy underscores the need for further exploration of the barriers and facilitators of effective hand hygiene practices within the university setting [ 11 , 24 , 31 ]. The successful implementation of infection control depends critically on two factors: the method’s capability to decrease the pathogen count and the accessibility of the technique to the involved participants.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations